INSTITUTIONAL HISTORICITY OF NURSING TEACHING IN PARAÍBA STATE/BRAZIL: A CONTRIBUTION FOR THE STUDY - Daísy Vieira de Araújo; Cesar Cavalcanti da Silva (Universidade Federal do Paraná, 2007)
The present study is an excerpt of the dissertation for the author's master's degree and objectifies to track down thehistorical trail of nursing teaching in Paraíba State/Brazil, focusing on institutional transformations that determined changes in thenursing graduation course of the Center of Health Sciences at the Federal University of Paraíba - CCS/UFPB. It promotes an incursionon nursing teaching in Brazil, from the creation of courses for nursing assistants, technical courses up to the superior level, reportingthe main historical events in Paraíba State. It is an updating article that intends to analyze the state- of- the- art process for nursingprofessional qualification in João Pessoa-Paraíba State, elucidating the underlying legislation.